Characterization of the elemental distribution of superalloy composite powders by micro beam X-ray fluorescence and laser-induced breakdown spectroscopy - Li, Dong-ling; Liu, Zong-xin; Zhao, Lei; Shen, Xue-jing; Wang, Hai-zhou (Spectrochimica acta. Part B: Atomic spectroscopy, 2020)
During the mechanical mixing of many types of powders, mechanical alloying will occur between powders of different components and particle sizes, accompanied by a series of complex physical and chemical changes. In this study, micro beam X-ray fluorescence (μ-XRF) and laser-induced breakdown spectroscopy (LIBS) were used to analyze the surface composition distribution and depth profile of cobalt and superalloy composite powders mixed for different ball-milling times. In addition, the variation of the content of the metal composite powders from the surface to the interior was determined. X-ray diffraction, scanning electron microscopy combined with energy-dispersive X-ray spectroscopy, and inductively coupled plasma atomic emission spectrometry were also used to characterize the morphology, structure, and the average content of the composite metal powders. The effects of the ball-milling time on the morphology, composition distribution, and microstructure of the composite metal powder were studied. Increasing ball-milling time led to improvement of the dispersion of cobalt powder in the superalloy composite. Fine cobalt particles were gradually attached to the surface of large superalloy particles by the mechanical alloying process. The cobalt contents determined by μ-XRF were clearly higher than the designed values owing to cobalt enrichment on the surface of the powder particles. Depth distribution analysis by LIBS also indicated the occurrence of cobalt segregation in the outer layer of composite particles with an enrichment thickness of normally less than 10 μm. [Display omitted] •The surface-composition distribution of powders was measured by μ-XRF.•The powder sample was prepared as a pellet before determined by LIBS.•The segregation of cobalt was determined by depth profiling using LIBS.•Cobalt powder dispersed uniformly in powders after ball milling for 24 h.•Co enrichment on particle surface led to a higher content than designed values.